Разработка термических деаэраторов повышенного давления для турбоустановок энергоблоков АЭС мощностью 1200 МВт - Григорьев, Г. В.; Егоров, П. В.; Чупраков, М. В.; Гиммельберг, А. С.; Сухоруков, Ю. Г. (НТУ "ХПИ", 2014)
С учетом опыта создания и внедрения деаэраторов для Тяньваньской АЭС в Китае и АЭС «Куданкулам» в Индии, разработаны новые деаэраторы производительностью 6400 т/ч для энергоблоков №1, 2 мощностью 1200 МВт Нововоронежской АЭС-2 и Ленинградской АЭС-2 проекта АЭС-2006. Результаты разработки и освоения указанных деаэраторов используются при проектировании новых деаэраторов для энергоблоков №1, 2 мощностью 1200 МВт Белорусской АЭС, а также перспективных энергоблоков АЭС и ТЭС в России и за рубежом.

Based on the experience gained in the design and commercialization of the deaerators for the Tian Van Nuclear Power Station in China and Nuclear Power Station "Cudanculum" in India we developed new deaerators with the capacity of 6400 t/h for the power units No1 and 2 of 1200 MW for Novovoronezh NPS-2 and Leningrad NPS-2 under the project NPS-2006. The structure of new deaerators has many advantages, in particular the capacity was increased, the rated content of oxygen in the deaerated water was decreased, and the technological effectiveness during the manufacture and assembly on the site of nuclear power station has been improved. The results of the development and operation of new deaerators are used for the design of new deaerators for the power units No 1 and 2 of 1200 MW intended for the Byelorussian NPS and also rather promising power units for NPS and TPS in Russian and abroad.
Development of the thermal deaerators of high pressure for the turbine plants of the power units of nuclear power stations
Keywords: низконапорное водораспределительное устройство; деаэратор питательной воды; low-head water distribution unit; Project NPS-2006; feed water dearator